Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.8 - Solving Equations by Factoring and Problem Solving - Exercise Set - Page 323: 68



Work Step by Step

Using properties of equality, the solution to the given expression, $ -4(a+1)-3a=-7(2a-3) $, is \begin{array}{l} -4a-4-3a=-14a+21 \\\\ -7a+14a=21+4 \\\\ 7a=25 \\\\ a=\dfrac{25}{7} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.